Studi Metodologi Tafsir Asy-Sya’rawi - Hikmatiar Pasya (Studia Quranika, 2017)
Understanding of Qur'an will always relate or have some correlation to the development of a human’s life. As stated by Umar ibn Khathab, "I go out from Qur'an in order to return to it." It means we must apply a contextual approach and not just textual to substantially understand Qur'an. In the middle of this pluralistic society, Sya'rawi was born. His consistency in explaining Qur'an with the Qur'an itself, expresses a realization in his perspective that the most accurate method in explaining the Qur'an is by using the Qur'an itself (al-Qur’an yufassiru ba’duhu ba’dhan). By using adabi and i’jazi methods in interpretating Qur'an, it is hoped to be a solution for these issues, so Qur'an and Islam will always be as shâlih likulli zamân wa al-makân.